2022
DOI: 10.21203/rs.3.rs-2187166/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decellularized placental sponge as an excellent carrier for human mesenchymal stem cells and management of full-thickness skin wounds: an in vitro and in vivo study

Abstract: Skin injuries lead to a large burden of morbidity. Although numerous clinical and scientific strategies have been investigated to repair injured skin, optimal regeneration therapy still poses a considerable obstacle. To address this challenge, the decellularized extracellular matrix-based scaffolds recellularized with stem cells offer significant advancements in skin regeneration and wound healing. Herein, a decellularized human placental sponge (DPS) was fabricated using the decellularization and freeze-dryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…They provide the necessary three-dimensional structure and mechanical strength to support bone formation. , Recruitment of stem cells from the synovial fluids cannot help bone regeneration when the microenvironment is unsuitable for cell adhesion . Furthermore, ECM scaffolds have demonstrated their potential to induce or support vascularization, creating an osteoinductive microenvironment that enhances bone tissue engineering. ,, It has been indicated that placental growth factors can support the osteogenic differentiation of mesenchymal cells . The healing process around implanted scaffolds involves interactions of multiple cell types, including inflammatory cells, such as macrophages and cells of mesenchymal origin. , MSCs are particularly significant due to their role as progenitors of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide the necessary three-dimensional structure and mechanical strength to support bone formation. , Recruitment of stem cells from the synovial fluids cannot help bone regeneration when the microenvironment is unsuitable for cell adhesion . Furthermore, ECM scaffolds have demonstrated their potential to induce or support vascularization, creating an osteoinductive microenvironment that enhances bone tissue engineering. ,, It has been indicated that placental growth factors can support the osteogenic differentiation of mesenchymal cells . The healing process around implanted scaffolds involves interactions of multiple cell types, including inflammatory cells, such as macrophages and cells of mesenchymal origin. , MSCs are particularly significant due to their role as progenitors of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“… 74 Furthermore, ECM scaffolds have demonstrated their potential to induce or support vascularization, creating an osteoinductive microenvironment that enhances bone tissue engineering. 15 , 75 , 76 It has been indicated that placental growth factors can support the osteogenic differentiation of mesenchymal cells. 77 The healing process around implanted scaffolds involves interactions of multiple cell types, including inflammatory cells, such as macrophages and cells of mesenchymal origin.…”
Section: Discussionmentioning
confidence: 99%